PROSPECTS FOR TOURISM DEVELOPMENT IN UZBEKISTAN AND ITS ECONOMIC POTENTIAL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the contribution of Uzbekistan\’s tourism sector to economic development. It discusses how comprehensive tourism development can support economic growth, create new jobs, attract investment, and modernize infrastructure. Special attention is paid to integration with other sectors as well as to the principles of ecotourism and sustainable development. The paper also highlights Uzbekistan\’s opportunities and prospects for tourism development.